B production in Z decays - Abreu,P; Adam,W; Adye,T; Agasi,E; Ajinenko,I; Aleksan,R; Alekseev,GD; Allport,PP; Almehed,S; Alvsvaag,SJ; Amaldi,U; Amato,S; et al. (Zeitschrift Fur Physik C Particles and Fields, 1995)
The decay B→Bγ has been observed with the DELPHI detector at LEP, where the B meson is produced in Z boson decays. The combination of inclusively reconstructed B mesons with well-measured converted photons yields a measurement of the flavour-averaged B-B mass difference of 45.5±0.3 (stat.) ±0.8 (syst.) MeV/c2. 95% confidence level upper limits at 6 MeV/c2 are placed on both the isospin (i.e. B+-B0) and the Bs-Bud splitting of the mass difference. The production ratio of B to B mesons in Z decays is measured to be 0.72±0.03 (stat.) ±0.06 (syst.). Limits on the production cross-section of other hypothetical excited B hadron states decaying radiatively are established. The differential B cross section has been measured to be in good agreement with the average b fragmentation, yielding an average fractional B energy of xE=0.695±0.009 (stat.) ±0.013 (syst.). From the decay angular distribution the relative contribution of longitudinal B polarisation states is measured to be σL/(σL + σT) = 0.32 ± 0.04 (stat.) ±0.03 (syst.). © 1995 Springer-Verlag.